Liquid 3He-4He mixture phase diagram in restricted geometry - Degtiarov, I.A.; Sokolov, S.S. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
The influence of van der Waals forces on the decay of liquid solutions of helium isotopes is studied theoreticallyand the conditions for the phase co-existence in a confined geometry are investigated. As the models to accountthe influence of van der Waals forces on the helium isotope solution the gap between two parallel planes and the cylindrical channel are considered. For each of the models we calculated the concentration profile inside the channel depending on the van der Waals constant, the initial solution concentration and the size of the channel. The phase diagrams of liquid solutions are constructed. The obtained liquid mixture phase diagrams are compared with the “bulk” phase diagram. A rather good agreement between theoretical and experimental phase diagrams is obtained for liquid helium mixture in aerogel.